Pig’s Liver Rice Crepes: A 1970s Edmonton Dim Sum Ticket - Lieffers, Caroline; Wong, Jason (Cuizine, 2014)
This article examines a dim sum ticket from the My Lai Garden, a prominent 1970s Edmonton restaurant, arguing that this traditional Cantonese assortment of snacks and tea acted as a transplanted cultural space for a transplanted people. As Edmonton’s Chinese population exploded in the 1970s, dim sum worked as an ethnic performance and a social space, a cultural metaphor and a practical occasion for families to bond, friends to meet, and business to be transacted. At the same time, dim sum at the My Lai Garden offered opportunities for inclusion and exchange, attracting Euro-Canadian diners intrigued by its worldly connotations. The restaurant, however, did not simply dish up a commoditized ethnicity: the ritual’s defining Chineseness and subtle cultural meanings remained elusive to non-Chinese outsiders. Dim sum, prepared principally by and for the Chinese community, exists and persists with or without Euro-Canadians, complicating questions of cultural hegemony and suggesting a more complex history of ethnic life in Edmonton.